Challenges to soya export promotion: An institutional analysis of trade policy in Malawi - Aberman, Noora-Lisa; Edelman, Brent (International Food Policy Research Institute, 2014)
This study undertakes an institutional analysis of the soya export sector in Malawi to determine the critical institu-tional barriers to engaging in and expanding soya exports. Institutional economics allows for the study of both formal and informal rules, examining the impact of both on transaction costs and resultant actor behavior.